Рівень тривожності молодших школярів, які займаються настільним тенісом - Кушнір, Василь Васильович; Фотуйма, Олександр Ярославович; Kushnir, Vasily; Futuyma, Alexander (Східноєвропейський національний університет імені Лесі Українки, 2015)
Більшість досліджень, що стосуються настільного тенісу, спрямовані на спорт вищих досягнень. Молодші школярі готові сприймати та з інтересом ставитися до нововведень щодо настільного тенісу не лише як до гри, і як підвідних спеціальних вправ із м’ячем і ракеткою. У статті висвітлено рівень тривожності молодших школярів, котрі займаються настільним тенісом. При цьому розглянуто тривожність як один зі станів емоційно-вольового компонента психічної готовності майбутніх тенісистів. Визначено критерії, що безпосередньо впливають на формування рівня тривожності крізь призму факторного аналізу. Шкали соціальної бажаності не розглядалися нами. З’ясовано, що в більшості дітей 8–10 років наявний нормальний рівень розвитку тривожності. Нагальний індивідуальний підхід під час тренувальної й змагальної діяльності щодо тих тенісистів, котрим не властива тривожність чи її рівень дещо підвищений. Диференційовано відмінності у факторах впливу на рівень тривожності між хлопцями та дівчатами. Отримані результати формують загальне уявлення про стан тривоги юних тенісистів і дають змогу в індивідуальному порядку вносити корективи в процесі тренувальної та змагальної діяльності. Визначення рівня тривожності – компонент комплексного відбору дітей у групи початкової підготовки. Most studies on tennis, aimed at elite sport. Younger students are willing to accept with interest relate to innovation in table tennis, not necessarily as a game but as a special submarine exercises with the ball and racket. The article highlights the anxiety level of junior high school students who are engaged in table tennis. This anxiety is regarded as one of the states of emotional and volitional components of mental readiness of the future tennis players. The results. The criteria, which directly influence the formation of the level of anxiety in the light of the factor analysis. The scale of social desirability was not considered in the study. It was found that the majority of children of 8–10 years has normal levels of anxiety. Relevant is the individual approach during training and competitive activity of tennis which is not peculiar to her level of anxiety or slightly increased. Findings. After some investigation to determine the level of anxiety in younger students during the competition, it should be noted that the presence of which is necessary for adaptation and productivity of both girls and boys. There is an urgent personal approach during training and competitive activity of tennis players about whom no inherent or her anxiety level increased slightly. Factor analysis points to the differences between boys and girls in the criteria influencing the level of anxiety and allows you to make adjustments on interviews with children focus before games to improve a competitive success at an early stage of the competition. Determining the level of anxiety is a component of a comprehensive selection of children in basic training.
The Level of Anxiety of Younger Students who Are Engaged in Table Tennis
Keywords: рівень тривожності; змагальна діяльність; факторний аналіз; молодші школярі; anxiety; competitive activity; factor analysis; primary school age